2023
DOI: 10.1002/smll.202207204
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots with Guanidinium and Amino Acid Functional Groups for Targeted Small Interfering RNA Delivery toward Tumor Gene Therapy

Abstract: Small interfering RNA (siRNA)‐based gene therapy represents a promising strategy for tumor treatment. Novel gene vectors that can achieve targeted delivery of siRNA to the tumor cells without causing any side effects are urgently needed. To this end, the large amino acid mimicking carbon dots with guanidinium functionalization (LAAM GUA‐CDs) are designed and synthesized by choosing arginine and dopamine hydrochloride as precursors. LAAM GUA‐CDs can load siRNA through the multiple hydrogen bonds between their g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Simultaneously, the amino acid cluster at the edge of LAAM GUA-CDs imparts them with tumor-targeting ability, thus providing a versatile strategy for tumor-targeted siRNA delivery and cancer therapy owing to a versatile strategy. 451 He et al reported that hyaluronic acid in hyaluronic acidmodified CDs (HA-CDs) acted not only as a CDs component but also as a hydrophilic group and targeting ligand. HA-CDs loaded doxorubicin (HA-CD@p-CBA-DOX) via an acid cleavage bond, released the drug in a pH-responsive manner, and exhibited good hemocompatibility and serum stability while exhibiting high cytotoxicity against 4T1 tumor cells.…”
Section: Chemicalmentioning
confidence: 99%
See 4 more Smart Citations
“…Simultaneously, the amino acid cluster at the edge of LAAM GUA-CDs imparts them with tumor-targeting ability, thus providing a versatile strategy for tumor-targeted siRNA delivery and cancer therapy owing to a versatile strategy. 451 He et al reported that hyaluronic acid in hyaluronic acidmodified CDs (HA-CDs) acted not only as a CDs component but also as a hydrophilic group and targeting ligand. HA-CDs loaded doxorubicin (HA-CD@p-CBA-DOX) via an acid cleavage bond, released the drug in a pH-responsive manner, and exhibited good hemocompatibility and serum stability while exhibiting high cytotoxicity against 4T1 tumor cells.…”
Section: Chemicalmentioning
confidence: 99%
“…Compared with other sensing and imaging materials, such as semiconductor quantum dots and organic molecules, 0D CNMs exhibit low toxicity and high biocompatibility, which are the most important properties both in vitro and in vivo . Although unpurified fullerenes are cytotoxic, no toxicity was detected after the fullerenes were extensively purified, even if the concentration is increased by 100,000 times, and purified fullerenes even exhibit considerable cell protection and, thus, have been widely used in medicines and cosmetics for removing free radicals and ROS on the skin surface and inside the human body. , CNOs are much less toxic than CNTs and show excellent cell survival rates, even at relatively high concentrations . NDs have been used as artificial joints for the human body, contact lens solutions, dental materials, nanomedicines, and biological-labeling sensors, which provide persuasive evidence for their low toxicity and high biocompatibility. ,, In comparison, the toxicity and biocompatibility of CDs have been confirmed by more reports, in which not only the in vitro MTT, CCK-8, and WST-1 methods indicated wonderful cell viability after culturing and treatment with CDs but also different cellular components of tissue structures in various organs were negligibly damaged and maintained good vitality. , Because CDs are usually easily metabolized and excreted from the body, certain CDs toxicities can only be detected after a very prolonged deposition or at extremely high concentrations. , …”
Section: Optical Properties Of 0d Cnmsmentioning
confidence: 99%
See 3 more Smart Citations